Top tips and pitfalls in revision knee arthroplasty surgery. Issue 1 (February 2017) - Porteous, Andrew
Abstract: Revision knee replacement is challenging for the patient and surgeon alike, but providing a clear cause for failure of the primary prosthesis is identified, then good improvement and outcome can be achieved. Patient selection and diagnosis are important factors in making the decision to revise a knee. Specific aspects of history taking, examination and investigations are discussed to allow the surgeon to recognize patterns of failure that may be amenable to surgery. Once a decision to proceed to revision has been made, the important aspects of pre-operative planning and our protocol for surgical reconstruction are described. In standard revisions, it should be possible to achieve the same alignment, sizing, balance, stability, fixation and joint line restoration as a primary knee replacement, with the expectation of a very good outcome. In multiply revised, infected or stiff knees, or where there is significant bone loss, compromises may need to be made to prioritize fixation and stability over aiming for normality. The vast majority are still improved by surgery, but expectations should be lowered for this salvage group of patients.